Dance Preparation: Kinesthetic Exercise to Improve Jaranan Dancing Ability Extracurricular in Elementary School - Ridho Rijaly; Atip Nurharini (MIMBAR PGSD Undiksha, 2023)
Often, students experience injuries and low-quality performance caused by low fitness and physical training. After digging deeper, fitness and physical activity rarely occur before Jaranan dance practice begins. This research aims to analyze the impact that occurs after elementary school students carry out the kinesthetic training process regularly and correctly. This research uses descriptive qualitative research with a qualitative approach. The data collection techniques used in this research are observation, in-depth interviews, documentation, and data analysis. Data validation techniques include triangulation of sources and methods. This research shows that providing kinesthetic training to elementary school students through a series of kinesthetic exercises for the Jaranan dance can improve flexibility, balance, and muscle strength and make the body ready to practice the Jaranan Dance. Kinesthetic training has a direct impact on increasing muscle readiness as preparation before being able to dance the Jaranan Dance, so it also has an effect on improving training performance and Jaranan dance performances. With this, students can coordinate their body movements so that kinesthetic training is needed in the learning process. It is hoped that students can strengthen their physical abilities through kinesthetic exercises carried out in stages. The research results can be input for various parties to improve kinesthetic training to improve Jaranan Dance skills in extracurricular dance learning, especially Jaranan Dance.